The Role Of E-Commerce In Indian Trade - Kumar Gupta, Dr. Pradeep (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
There is a need to generate much greater awareness about e-commerce and its benefits. An appropriate communication strategy needs to be formulated to spread e-commerce awareness among enterprises by underscoring the benefits and dispel any misconceptions. The apex industry bodies like the CM should coordinate with themselves and the Government to educate people in decision-making positions in Indian organizations. IT education would be a major driving force towards the development, adoption and growth of e-commerce in India. Keywards:Revenue, e-commerce, IT.